Comparative study of a novel proximal femoral bionic nail and three conventional cephalomedullary nails for reverse obliquity intertrochanteric fractures: a finite element analysis - Yang, Yanjiang; Tong, Yu; Cheng, Xiaodong; Zhu, Yanbin; Chen, Wei; Cui, Yunwei; Zhang, Qi; Zhang, Yingze (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: Conventional cephalomedullary nails (CMNs) are commonly employed for internal fixation in the treatment of reverse obliquity intertrochanteric (ROI) fractures. However, the limited effectiveness of conventional CMNs in addressing ROI fractures results in significant implant-related complications. To address challenges associated with internal fixation, a novel Proximal Femoral Bionic Nail (PFBN) has been developed. Methods: In this study, a finite element model was constructed using a normal femoral specimen, and biomechanical verification was conducted using the GOM non-contact optical strain measurement system. Four intramedullary fixation approaches-PFBN, Proximal Femoral Nail Antirotation (PFNA), InterTan nail (ITN), and Gamma nail (GN)-were employed to address three variations of ROI fractures (AO/OTA 31-A3). The biomechanical stability of the implant models was evaluated through the calculation of the von Mises stress (VMS), contact pressure and displacement. Results: Compared to conventional CMNs, the PFBN group demonstrated a 9.36-59.32% reduction in the maximum VMS at the implant. The A3.3 ROI fracture (75% bone density) was the most unstable type of fracture. In comparison to conventional CMNs, PFBN demonstrated more stable data, including VMS values (implant: 506.33 MPa, proximal fracture fragment: 34.41 MPa), contact pressure (13.28 MPa), and displacement (17.59 mm). Conclusion: Compared to the PFNA, ITN, and GN, the PFBN exhibits improvements in stress concentration, stress conduction, and overall model stability in ROI fractures. The double triangle structure aligns better with the tissue structure and biomechanical properties of the proximal femur. Consequently, the PFBN has significant potential as a new fixation strategy for the clinical treatment of ROI fractures.